R-loops promote antisense transcription across the mammalian genome - Tan-Wong, SM; Dhir, S; Proudfoot, N (Elsevier, 2019)
Widespread antisense long noncoding RNA (lncRNA) overlap with many protein-coding genes in mammals and emanate from gene promoter, enhancer, and termination regions. However, their origin and biological purpose remain unclear. We show that these antisense lncRNA can be generated by R-loops that form when nascent transcript invades the DNA duplex behind elongating RNA polymerase II (Pol II). Biochemically, R-loops act as intrinsic Pol II promoters to induce de novo RNA synthesis. Furthermore, their removal across the human genome by RNase H1 overexpression causes the selective reduction of antisense transcription. Consequently, we predict that R-loops act to facilitate the synthesis of many gene proximal antisense lncRNA. Not only are R-loops widely associated with DNA damage and repair, but we now show that they have the capacity to promote de novo transcript synthesis that may have aided the evolution of gene regulation.